Front Cover Picture: HFIP‐Mediated Decarboxylative [4+3]‐Annulation of Azaoxyallyl Cations with Isatoic Anhydride (Adv. Synth. Catal. 17/2020). Issue 17 (21st July 2020) - Kim, Eunjin; Lee, Chang Yoon; Kim, Sung‐Gon
Abstract : The front cover picture, provided by Sung‐Gon Kim and his co‐workers, illustrates an efficient [4+3]‐annulation reaction between in situ generated azaoxyallyl cations and isatoic anhydride to afford seven‐membered 1, 4‐benzodiazepinediones. This annulation involves the cascade reaction of decarboxylative addition of hexafluoroisopropanol (HFIP) to isatoic anhydride, addition to the azaoxyallyl cation generated from α‐halohydroxamate, and intramolecular substitution to yield 1, 4‐benzodiazepinediones. Details of this work can be found in the full paper on pages 3594–3603 (E. Kim, C. Y. Lee, S.‐G. Kim, Adv. Synth. Catal . 2020, 362, 3594–3603; DOI: 10.1002/adsc.202000439 ).